Konservasi Bangunan Cagar Budaya Berbasis Status Kepemilikan: Gedung Oudetrap Dan Spiegel Di Kota Lama Semarang 2015-2022 - Safitri, Ika Novita; Alamsyah; Maziyah, Siti (PURBAWIDYA, 2025)
This research examines the conservation of heritage buildings based on ownership status of the Oudetrap and Spiegel buildings in the Old Town of Semarang during the period 2015-2022. The purpose of the research is to analyze the implementation of cultural heritage building conservation of the Oudetrap and Spiegel buildings from different ownership statuses. This research employs historical methods by collecting sources through in-depth interviews and several related conservation archives. This research takes two examples of building conservation, namely the Spiegel Building as one of the private properties that has been successfully revitalized since 2012 with clear and consistent ownership and repurposing into a commercially oriented building by 2015, and the Oudetrap Building as the only asset of the Semarang City government in the area managed for public interest, which also tends to prioritize historical value. This research shows that the ownership status of a building plays a significant role in determining the direction of conservation policies and the sustainability of cultural heritage preservation. This research is also complemented by a collaboration model between building owners, the government, and the community to create a balanced approach to the conservation of cultural heritage buildings, balancing historical value and preservation efforts. .